Effect of a biopesticide on some population parameters of the predator Delphastus pusillus (Coleoptera: Coccinellidae) - PÉREZ, RICARDO; GARCÍA-GONZÁLEZ, JAVIER; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2007)
In the design of pest management programs, an important aspect is to determine the compatibility between different control agents, for instance, between entomopathogenic fungi and the beneficial insects used for control of the same insect pest. Therefore the aim of this study was to establish the effect of a biopesticide based on the fungus Lecanicillium lecanii, an entomopathogen of the whitefly Trialeurodes vaporariorum, on some population parameters of the predator Delphastus pusillus. Through laboratory assays, we evaluated the effect of direct application of the biopesticide on survival of the adult stage of the predator. In a second experiment, life tables were constructed for the predator under two treatments: 1.Control, cohort of individuals fed healthy prey. 2. Cohort fed prey previously exposed to the biopesticide. In the direct application assay, it was determined that the biopesticide at the concentration recommended for whitefly control caused a mortality of 9.8% on the predators. In the life table experiment, results showed that the cohort of D. pusillus treated with the bioinsecticide had a significant reduction in longevity (49.0%) and fecundity (91.4%), with respect to the control. The results obtained suggest that application of the biopesticide could have moderate direct effects and important indirect effects on populations of D. pusillus.